Annuloaortic ectasia in a dog: long-term follow-up and immunofluorescent study. Issue 1 (1st January 2021) - Côté, Etienne; Zhang, Rong-Mo; Kaiser, Nicole; Reinhardt, Dieter P.; Martin, Chelsea K.
Abstract: A 4 month-old, 14.8 kg, male Newfoundland dog was presented for cardiovascular evaluation following detection of a heart murmur. Echocardiography revealed enlargement of the sinuses of Valsalva and marked, diffuse dilation of the ascending aorta (annuloaortic ectasia, AAE), with mild/equivocal subaortic stenosis (SAS). The dog was monitored over the duration of its lifetime, with serial echocardiograms performed at 5, 6, and 8 months and 1, 2, 3, 4, 8, and 10 years demonstrating persistent, diffuse dilation of the ascending aorta. The dog lived until it was 10 years old and died of metastatic carcinoma. Postmortem examination confirmed AAE and mild SAS. Hematoxylin and eosin and Weigert van Gieson stains were used to compare the ascending aorta to the descending aorta and left subclavian artery, and to compare aortic samples to those of three control dogs. Histopathologic evaluation revealed mild medial degeneration in the ascending aorta of all four dogs. Immunofluorescent microscopy was used for determining the deposition of proteins known to play a role in aortic aneurysms in humans: fibrillin-1 (FBN1), latent transforming growth factor beta binding protein 4 (LTBP4) and fibronectin. The ascending aorta of the AAE case demonstrated reduced deposition of FBN1, indicating that its loss may have contributed to aortic dilation. Diffuse, primary ascending aortic dilation is uncommonly reported in dogs; when it is, it carries a poor prognosis. This case provides an important example of marked dilation of the ascending aorta in a dog that lived with no associated adverse effects for 10 years.